Assessment of a toll plaza bridge using traffic microsimulation - Özturan, Tayfun. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Today, traffic congestion has been a problem leading into dramatic consequences, such as driver’s stress caused by waiting in the traffic, economic losses due to wasted time and oil, reduced quality of air because of the wasted oil and disproportionate pollutant emission and resulting in reduced quality of life for the drivers and the country. The objective of this study is to suggest solutions to minimize the total waiting time in the Fatih Sultan Mehmet Bridge toll plaza system which should result in reduced wasted oil consumption, pollutant emission, economic losses, and increased quality of life, using a microscopic traffic simulation software, AIMSUN. A model will be developed by coding the network of the Fatih Sultan Mehmet Bridge traffic system and traffic demand and control data observed from the field in the software. This will provide the users of the model and the decision makers an environment to experiment different toll plaza configurations and observe the outputs, which would be very expensive and very difficult to experiment in real life in the presence of the existing system. In the first part of the study, necessary data for the model are collected, statistical input data analysis is applied, the traffic system network model is developed, and the model is validated. In the second part, alternative toll plaza configuration designs are experimented, and according output data are recorded to five performance measures; toll plaza throughput, total system throughput, total delay, fuel consumption, and pollutant emission. In the final part of the study, the results of the alternatives are evaluated and compared with each other using statistical analysis techniques. The alternative, removing the extra lane, showed evident improvements. Fuel consumption is decreased by 61 per cent, total system throughput is increased by two per cent, pollutant emission is decreased by 76 per cent, total delay is decreased by 95 per cent, and throughput is increased by 2 percent.
Keywords: Traffic flow -- Mathematical models.; Computer simulation.